PEMANFAATAN MUSIK ROHANI DIGITAL DALAM PEMBENTUKAN KARAKTER DISIPLIN DAN SPIRITUAL SISWA SEKOLAH DASAR - Utomo, Yunatan Krisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the utilization of digital Christian music in shaping the disciplinary and spiritual character of elementary school students at Daniel Creative School. The study employed a descriptive qualitative case study approach with data collection techniques consisting of observation, semi-structured interviews, and documentation. The findings revealed that the use of digital Christian songs in learning activities, Time for Jesus, student worship services, and school habituation programs contributed to creating a more conducive learning atmosphere, improving students’ learning focus, emotional regulation, and participation in classroom activities. In addition, digital music media contributed to the development of students’ disciplinary character through positive habituation and structured learning routines. In the spiritual aspect, digital Christian songs helped students understand moral values such as gratitude, empathy, responsibility, and respect for others. The study demonstrates that digital Christian music can be developed as a character education strategy that is relevant to the digital culture of elementary school students in the contemporary digital era.